2021
DOI: 10.1021/acsomega.1c04257
|View full text |Cite
|
Sign up to set email alerts
|

Ultralong-Time Recovery and Low-Voltage Electroporation for Biological Cell Monitoring Enabled by a Microsized Multipulse Framework

Abstract: Long-term nondestructive monitoring of cells is of significant importance for understanding cell proliferation, cell signaling, cell death, and other processes. However, traditional monitoring methods are limited to a certain range of testing conditions and may reduce cell viability. Here, we present a microgap, multishot electroporation (M2E) system for monitoring cell recovery for up to ∼2 h using ∼5 V pulses and with excellent cell viability using a medium cell population. Electric field simulations reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 84 publications
2
8
0
Order By: Relevance
“…Perhaps the simplest explanation of the discrepancy is that there are two distinct mechanisms causing the impedance increase (Figure 5). The gradual increase we are measuring may be recovery and resealing of the cell membrane as reported in other studies ( 25, 29, 31, 32 ), but the response is shifted upward by a second mechanism that occurs rapidly. The second mechanism may be occurring only during the application of the electric field, which is a relatively brief period (∼0.2%) of the total observation period.…”
Section: Discussionsupporting
confidence: 64%
“…Perhaps the simplest explanation of the discrepancy is that there are two distinct mechanisms causing the impedance increase (Figure 5). The gradual increase we are measuring may be recovery and resealing of the cell membrane as reported in other studies ( 25, 29, 31, 32 ), but the response is shifted upward by a second mechanism that occurs rapidly. The second mechanism may be occurring only during the application of the electric field, which is a relatively brief period (∼0.2%) of the total observation period.…”
Section: Discussionsupporting
confidence: 64%
“…This behavior is consistent with that of previous calculations of lipid-bilayer models with constant electric fields. 6,64,65 We found that by comparison with the model after injecting the first electric-field pulse, the model after applying the second electric-field pulse exhibits a larger degree of membrane permeabilization, as indicated by a larger pore population (Fig. 1e and f).…”
Section: Resultsmentioning
confidence: 90%
“…Emerging and critical applications in fields, including genetic engineering, molecular medicine and gene therapy, require high-performance electroporation techniques for operations, such as food sterilization, 1 genetic payload transfer, 2 tumor ablation 3,4 and cell monitoring. 5,6 Next-generation electroporation techniques have therefore been an important subject of research. Moreover, some of the electroporation devices have made inroads into Covid-19 vaccine technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Electroporation disrupts the cell membrane by generating electric shock for intracellular nucleic acid delivery. Delivery efficiency can be improved by adjusting voltage, capacitance, resistance and other factors, such as cell number, density, RNA quantity and pulse time [ 53 , 72 , 73 ]. Electroporation has been used for DC-based mRNA vaccines in clinical trials [ 74 , 75 , 76 ].…”
Section: Delivery Vehiclementioning
confidence: 99%